2017
DOI: 10.1177/0748233716686916
|View full text |Cite
|
Sign up to set email alerts
|

Chest ultrasonography in health surveillance of asbestos-related lung diseases

Abstract: Chest US might be considered an additional tool to follow up subjects occupationally exposed to asbestos who have already undergone CT scan examination and whose pathology is detectable by US as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…For PE, it is known that Chest US can represent the gold-standard technique [18][19][20]. Inter-rater agreement with Chest X-ray showed a fair magnitude.…”
Section: Discussionmentioning
confidence: 94%
“…For PE, it is known that Chest US can represent the gold-standard technique [18][19][20]. Inter-rater agreement with Chest X-ray showed a fair magnitude.…”
Section: Discussionmentioning
confidence: 94%
“…Imaging studies play a pivotal role in the diagnosis and management of pleural disease, this study shows perfect and strong agreement between X-ray, CT and US in evaluation of amount of pleural effusion with moderate agreement between CT and US in evaluating the pattern of effusion even free or loculated with superiority of US which diagnose 40% of the cases in comparison with CT which diagnose 27% so the Chest US can represent the gold-standard technique (9) . This in agreement with Smargiassi et al (10) Who report US inter-rater agreement with Chest X-ray of a fair magnitude, Sobhyet al (11) study the ability to detect pattern of pleural effusion (free or loculated) and revealed that both CT and US were close to each other but with no significant difference.…”
Section: Discussionmentioning
confidence: 60%
“…For PE, it is known that Chest US can represent the gold-standard technique [1820]. Inter-rater agreement with Chest X-ray showed a fair magnitude.…”
Section: Discussionmentioning
confidence: 99%